Dispersi Kepemilikan, Pertumbuhan Penjualan, dan Kesulitan Keuangan terhadap Kebijakan Dividen yang Dimoderasi oleh Ukuran Perusahaan - Alfiana, Siti Tina; Ardhani, Lutfi (Jurnal E-Bis, 2024)
Indonesia, the largest archipelagic country, attracts both domestic and international tourists with its stunning natural beauty. The tourism sector has experienced significant growth, achieving a ranking of 32nd in the Travel and Tourism Development Index (TTDI) in 2022. This increase in tourist arrivals signals substantial business potential in the industry, drawing investors to various segments, including resort development, hotels, restaurants, and transportation infrastructure. The purpose of this research is to examine the influence of ownership dispersion, sales growth, and financial distress on dividend policy, with firm size as a moderating factor. A quantitative approach utilizing purposive sampling was employed, with data processed using STATA software. The findings reveal that only ownership dispersion significantly affects dividend policy, while firm size merely moderates the relationship between ownership dispersion and dividend policy. This highlights the importance of understanding ownership structures for optimizing dividend strategies in the tourism sector, fostering sustainable business growth.